SPEECH DEVELOPMENT IN RUSSIAN LANGUAGE LESSONS IN PRIMARY SCHOOL - Сейтбаева Гульхумар Бахадыр-кызы (European Science Publishing, 2023)
The article is devoted to the actual problem of speech development of younger schoolchildren in Russian language lessons. The main methods and techniques for the development of students' speech are considered, with the help of which the child will be able to improve his speech, mastering the riches of the language.
Keywords: Russian language, primary school students, development, speech.